Potassium and Cesium Fluorinated β-Diketonates: Effect of a Cation and Terminal Substituent on Structural and Thermal Properties - Danil V. Kochelakov; Evgeniia S. Vikulova; Natalia V. Kuratieva; Ilya V. Korolkov (Molecules, 2023)
As potential precursors for the synthesis of fluoroperovskites, a family of heavy alkali metal (MI = K, Cs) fluorinated β-diketonates were prepared and characterized by elemental analysis, IR, and powder-XRD. The crystal structures of the new six complexes, MI(β-dikF)(H2O)X, X = 0 or 1, were also determined. The structural diversity of this poorly explored class of complexes was discussed, including the preferred types of cation polyhedra and the ligand coordination modes, and the thermal properties of the metal β-diketonates were studied by TG–DTA in an inert (He) atmosphere. The data obtained allowed us to reveal the effect of the metal cation and the terminal substituent on the structural and thermal features of this family of complexes.